THE OX-BOW INCIDENT - Clark, Walter Van Tilburg, 1909-1971.; Graham, Lorenz; Nodel, Norman (Newbury, Berkshire : CCS Books, 2012)
A cowboy is unable to prevent three wandering travelers from being unjustly lynched for murder.
Primary.
Keywords: Clark, Walter Van Tilburg, -- 1909-1971. -- Adaptations; Lynching -- Comic books, strips, etc; Mobs -- Comic books, strips, etc; Nevada -- Comic books, strips, etc; Graphic novels; Comics adaptations